Social change and transformation as a developmental agenda in the South African higher education - Mvuyana, B. Y. C. (South African Journal of Higher Education, 2024)
The National Development Plan (NDP) advocates for the elimination of poverty, and the reduction of inequality by 2030. These goals can only be achieved if we harness the energies of the people, build an inclusive economy, develop skills, improve the capacity of the state and promote leadership and partnerships across society. This is to be achieved through transforming society more equitably and at the same time making the country more competitive in the global economic system. The article seeks to explore how institutions of higher learning can be transformed through the production of future professors with a developmental agenda. Therefore, the NDP advocates continuous professional development, lifelong learning and knowledge production, and innovation as a focus for building the capacity of individuals and society. The article employed the modernisation theory as a vehicle to drive social change and transformation in higher education. The article employed a systematic review of the literature on transformation and social change in higher education as advocated in the NDP. The findings of the article show that universal human development can be achieved by respecting human rights, promoting equality and empowering people to exercise the opportunities and choices they value in higher education. The article recommends that a structured interaction between lecturers and students within the context of transformative change and social justice should be prioritised in higher education. This can only be achieved through preparing the future professor with a developmental agenda to assist in shaping higher education by designing a curriculum that responds to the needs of the current cohort of students.